Path analysis of the effects of social support, self-efficacy, and coping style on psychological stress in children with malignant tumor during treatment. Issue 43 (23rd October 2020) - Liu, Qian; Mo, Lin; Huang, Xianqiao; Yu, Lu; Liu, Yang
Abstract : Abstract: The aim of this study was to explore the relationship between social support, self-efficacy, coping style, and psychological stress in children with malignant tumors during the treatment, and to clarify the mediating effects. From May 2019 to August 2019, selected by convenience sampling method, 141 children with malignant tumors in the treatment period were evaluated using the Social Support Questionnaire, General Self-efficacy Scale, Simplified Coping Style Questionnaire, and Depression-Anxiety-Stress Scale. The results of correlation analysis showed that depression was negatively correlated with coping style, self-efficacy, affirmation and support, satisfaction, company, and intimacy, but positively correlated with conflict and punishment; both anxiety and stress were significantly negatively correlated with coping style, self-efficacy, affirmation and support, company, and intimacy. The results of the model indicated that gender, social support, self-efficacy, and coping style could directly predict the psychological stress of children with malignant tumors in the treatment period, social support and self-efficacy could indirectly predict the psychological stress of children with malignant tumors, and the total effect of self-efficacy on the psychological stress of children was the largest. Through 2000 bootstrap tests of mediating effect, it not only confirmed the mediating effect of self-efficacy and coping style but also had a chain-mediating effect. Appropriate social support can improve the self-efficacy of children with malignant tumors in the treatment period and encourage them to take a positive response to the disease, thereby effectively preventing or reducing the occurrence of psychological stress.